2015
DOI: 10.1080/15402002.2015.1017101
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Differences by Race in Preschool Children: The Roles of Parenting Behaviors and Socioeconomic Status

Abstract: Sleep differences between Black and White preschool children were primarily mediated by parent behaviors rather than socioeconomic variables. Results may reflect differences in cultural practices and provide important information for treatment and parent-directed intervention regarding improving sleep in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
0
32
2
Order By: Relevance
“…A study by Patrick et al. () reported that black children have a later bedtime than white children. Similarly, Mindell et al.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Patrick et al. () reported that black children have a later bedtime than white children. Similarly, Mindell et al.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, unlike other intervention efforts, in this study parents did not receive specific information about age-appropriate sleep duration. Also of note, only intervention children had a nighttime sleep duration of 10 hours at follow-up, which aligns with the recommended sleep guidelines 7 for the age of the majority of children in this study sample (children ages [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5] Community-based studies have shown that Black preschoolers are more likely than their White peers to exhibit symptoms of behavioral sleep disturbances, such as increased bedtime resistance, longer sleep onset latency, and shorter total sleep duration. [5][6][7][8] Aspects of sleep routines and the sleep environment also differ by race, with Black children showing later bedtimes and decreased likelihood of following a regular bedtime routine, 5,6,8,9 as well as higher rates of parent-child bed-sharing. 10,11 Later bedtimes and less regular bedtime routines have been associated with increased child sleep disturbances, 2,12,13 and research on the effect of bed-sharing on child sleep is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The slightly later bedtimes and longer nap duration for Black children in this sample converge with previous research drawn from community-based samples. 3,[5][6][7][8] It may be that these results did not significantly differ from patterns of White children due to the nature of the clinically referred sample. It was striking that 16.1% of all children in our sample had reportedly consumed caffeine.…”
mentioning
confidence: 99%
See 1 more Smart Citation